Tawi-Tawi Regional Agricultural College Mandates: Instruction, Research, Extension, and Production - Juljani, Nurshima H (International Journal of Membrane Science and Technology, 2023)
The study sought to determine which of the four Tawi-Tawi Regional Agricultural College mandates had the most and least practical justifications. A quality and quantity descriptive-correlation design was used in the study. Research, instruction, extension services, and college productivity were the topics of the five parts of questions. The significance of the independent variables was assessed using multiple regression analysis. The majority of respondents were Muslim, female, from the Sama tribe, between the ages of 36 and 40, and single. The socioeconomic characteristics of the respondents did not indicate a significant impact on the efficiency of the institutions. A similar conclusion was made about production and extension services. The majority of the metrics used to gauge institutional performance received high marks. The college’s primary mandate was production, and its primary objective was instruction. Overall, all of the metrics received a "good" rating. This was suggested by the overall grand mean of 3.68. Three co-curricular program indicators were the only ones to obtain an overall rating of "very satisfactory." The indicators have qualified, capable faculty advisers for the numerous student organizations and clubs, and nominated officers methodically coordinate them. The socioeconomic characteristics of the respondents did not indicate a significant impact on the efficiency of the institutions. The college must have a tight admissions and retention policy. The latter group needs exceptional guidance in their extracurricular and academic endeavors.